El costo de la "remasterización" del Arbitraje - Estrada Rosas, Álvaro (2021)
As a result of the COVID-19 pandemic, arbitration has been forced to “remaster” itself, for which it has needed to implement the use of virtual tools. However, the implementation of technology in arbitration generates highly problematic issues or situations that are addressed in this article with the help of international guidelines on the use of technology in arbitration.